Universal Electric‐Field‐Driven Resistive Transition in Narrow‐Gap Mott Insulators. (6th May 2013) - Stoliar, Pablo; Cario, Laurent; Janod, Etiene; Corraze, Benoit; Guillot‐Deudon, Catherine; Salmon‐Bourmand, Sabrina; Guiot, Vincent; Tranchant, Julien; Rozenberg, Marcelo
<x xml:space="preserve">Abstract</x> A striking universality in the electric‐field‐driven resistive switching is shown in three prototypical narrow‐gap Mott systems. This model, based on key theoretical features of the Mott phenomenon, reproduces the general behavior of this resistive switching and demonstrates that it can be associated with a dynamically directed avalanche. This model predicts non‐trivial accumulation and relaxation times that are verified experimentally. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>